Situation Report: Romania, 18 April 1986 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe/Radio Liberty based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Romania's German Minority New Developments in the Harassment of Ethnic German Writers / by Dan Ionescu Workers' Hostels / by Dan Ionescu Pensioners Barred from Moving to Large Cities / by Anneli Maier The Latest in a History of Mining Disasters / by Paul Gafton The 1986 State Budget / by Paul Gafton From Tractor to Horse and Back / by Carmen Pompey Romanian Foreign Minister Visits Teheran Children Questioned on Religious Influence